Marketing Communication Strategy of Organic Argotourism Beji Makmur by Gapoktan in Increasing the Number of Visitors in Wonogiri - Siti Aminah; Pawito; Mahendra Wijaya (Formosa Journal of Social Sciences (FJSS), 2023)
The development of tourism objects in Beji cannot be separated from the role of the local Gapoktan. Gapoktan's main obstacle in promoting organic village tourism is the lack of knowledge about using social media. The purpose of this study was conducted to determine the marketing communication strategy for Beji Makmur organic agrotourism by Gapoktan in increasing the number of visitors to Wonogiri. The method used in this research is a qualitative research method. This type of research uses a qualitative descriptive type. The informants interviewed were Gapoktan, PPL and visitors. The results of this study are Gapoktan as the manager in carrying out the marketing communication strategy for Organic Agrotourism in increasing the number of visitors including three marketing activities, namely first promotion, the second is personal selling and then the third is public relations activities